Strategi dan Sistem Pembinaan Prestasi Pada Akademi Futsal Jatidiri Muda Kota Semarang Tahun 2024 - Muammar, Rofi; Nurrachmad, Limpad (Innovative: Journal Of Social Science Research, 2025)
This study discusses the management of futsal sports coaching with a focus on aspects of management, achievement coaching, and human resource development in futsal clubs and related sports institutions. Based on the literature review conducted, it is known that effective management in futsal sports includes several important dimensions, including athlete coaching strategies, human resource management, adequate facilities and infrastructure, and ongoing evaluation. This study also highlights the importance of the role of coaches and organizations in improving futsal team performance, both at regional and national levels. Futsal sports achievement coaching, which is carried out through early childhood training and development centers, is one of the main keys to achieving long-term success. In addition, evaluations of coaching programs also show that success in futsal sports is greatly influenced by professional management and integration between physical, technical, and mental training aspects. This study also notes that structured and ongoing coaching can have a positive impact on producing high-achieving athletes, especially in competitive events such as PON, Porprov, and the national futsal league.